Alat Pengukuran Dan Faktor Yang Mempengaruhi Evaluasi Kinerja: Sebuah Studi Literatur - Jauharul Makhnun, Intan; Trisnaningsih, Sri (Fakultas Ekonomi Universitas Gresik, 2023)
Conceptual evaluation is the process of evaluating a concept or idea to determine whether the concept meets predetermined criteria or not. Concept evaluation is often done before product or project development begins. This study focuses on measurement tools and factors that influence performance evaluation in management, accounting, and business journals published in international journals and sinta journals, published in 2018 - 2023. It is very important to capture the development direction of performance evaluation research, especially in accounting, management, and business. This research was conducted by reviewing published literature reviews in Google Scholar, Scopus, and Sinta Journal. Literature review or literature review is a research method that is carried out by conducting studies, analysis, and evaluation of previously published papers on the research topic being carried out. Employee performance measurement tools may vary depending on the purpose of the performance evaluation and the characteristics of the organization in which the employee works. Organizations or companies also often use a balanced scorecard. In particular sales growth, measurement can also be done using the Sales Satisfication Index. Then several theories are used in research on factors that influence employee performance, including: motivation theory, expectancy theory, social learning theory, equity theory, engagement theory